Tobacco control policies and smoking behavior in Europe: More than trends? - Reto Odermatt; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2018)
In many European countries, there is an unmissable trend towards stricter tobacco control policies and a parallel reduction in the prevalence of smoking. The extent to which policies promote this latter trend, however, is less clear. We therefore analyze the staggered introductions of smoking bans and the variation in cigarette taxes over more than twenty years. After taking into account unobserved country- and time-specfiic effects as well as country-specific trends, we find no clear evidence that smoking bans are associated with lower levels of smoking. In contrast, higher cigarette prices tend to be negatively related to smoking, in particular for men and people under the age of 30. However, price elasticities are small. Overall, the results suggest that only about one sixth of the decline in the prevalence of smoking in Europe can be explained by our policy variables.
Keywords: D12; H31; I18; K32; 330; smoking bans; cigarette taxes; smoking behavior; tobacco control policies